Docking applied to the study of inhibitors of c-Met kinase - Gavernet, Luciana (2012)
Quinoxaline derivatives were studied as inhibitors of c-Met kinase, a receptor associated with high tumor grade and poor prognosis in a number of human cancers. In this investigation we used docking methodologies to predict the binding conformation of a set of quinoxalines and to explain the differences of biological activities previously reported.